Long non‐coding RNA SNHG6 promotes cell proliferation and migration through sponging miR‐4465 in ovarian clear cell carcinoma. Issue 8 (22nd May 2019) - Wu, Yong; Deng, Yu; Guo, Qinhao; Zhu, Jun; Cao, Lijie; Guo, Xueqi; Xu, Fei; Weng, Weiwei; Ju, Xingzhu; Wu, Xiaohua
Abstract: Dysregulation of small nucleolar RNA host gene 6 (SNHG6) exerts critical oncogenic effects and facilitates tumourigenesis in human cancers. However, little information about the expression pattern of SNHG6 in ovarian clear cell carcinoma (OCCC) is available, and the contributions of this long non‐coding RNA to the tumourigenesis and progression of OCCC are unclear. In the present study, we showed via quantitative real‐time PCR that SNHG6 expression was abnormally up‐regulated in OCCC tissues relative to that in unpaired normal ovarian tissues. High SNHG6 expression was correlated with vascular invasion, distant metastasis and poor survival. Further functional experiments demonstrated that knockdown of SNHG6 in OCCC cells inhibited cell proliferation, migration and invasion in vitro as well as tumour growth in vivo. Moreover, SNHG6 functioned as a competing endogenous RNA (ceRNA), effectively acting as a sponge for miR‐4465 and thereby modulating the expression of enhancer of zeste homolog 2 (EZH2). Taken together, our data suggest that SNHG6 is a novel molecule involved in OCCC progression and that targeting the ceRNA network involving SNHG6 may be a treatment strategy in OCCC.